Cocoa of Excellence Programme provided visibility and improved processing techniques and final quality - CGIAR Research Program on Forests, Trees and Agroforestry (2018)
The Cocoa of Excellence Programme has been recognized by participants in facilitating connection between cocoa producers and other relevant stakeholders, providing not only an international platform and major visibility, but also tools to improve fermenting and roasting techniques. The Programme is considered a unique way to promote cocoa diversity and expression of terroir, putting at the centre the cocoa producer. The promotion of high quality cocoa linked to the work done at farm level has potential to improve farmers livelihood in the long term.